Environmentally friendly complex enhanced composite pipe and preparation method thereof

By adding ionic complexing agent to PVC resin, an environmentally friendly complex reinforced composite pipe is formed, which solves the problem of insufficient cold resistance and impact resistance of PVC pipes at low temperatures, and improves the thermal stability and mechanical properties of the material. .

CN118480238BActive Publication Date: 2025-02-11HANGZHOU GUANKANG PLASTIC IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410809340.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-21
Publication Date
2025-02-11
Estimated Expiration
2044-06-21

AI Technical Summary

Technical Problem

The existing PVC pipes have poor cold resistance and impact resistance in low temperature environments, and are prone to becoming brittle and damaged.

Method used

By adding ionic complexing agent to the PVC resin, an environmentally friendly complex reinforced composite pipe is formed to prevent the precipitation of calcium and zinc thermal stabilizers during processing, thereby improving the thermal stability and mechanical properties of the material.

Benefits of technology

The impact resistance and weather resistance of PVC pipes at low temperatures are improved, the problem of precipitation of calcium and zinc thermal stabilizers is avoided, and the overall performance of the material is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an environmentally friendly complex-enhanced composite pipe and a preparation method thereof, belonging to the technical field of PVC pipes. The composite pipe comprises the following components by weight: 60-100 parts of PVC resin and 3-5 parts of an ion complexing agent, wherein the ion complexing agent is a mixture of a calcium-zinc composite stabilizer, titanium dioxide, a lubricant, nano-calcium carbonate, methyl acrylate and a plasticizer; the calcium-zinc composite stabilizer is improved so that it can be better combined with a material matrix, and the migration and precipitation of a processing aid during processing are reduced. The composite pipe obtained by the invention has strong weather resistance and good impact resistance at low temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PVC pipes, and in particular to an environmentally friendly complex-enhanced composite pipe and a preparation method thereof. Background Art

[0002] Polyvinyl chloride (PVC) is the world's second largest general-purpose resin, and its output is second only to polyethylene (PE). PVC is inexpensive and has the advantages of corrosion resistance, aging resistance, excellent mechanical properties, good electrical insulation and flame retardancy. Its products are widely used in construction, chemical, electrical appliances and other industries, mainly in the production of pipes, profiles, plates, leather, films and other products.

[0003] The PVC pipes currently used in the market have good insulation, pressure resistance, impact resistance, corrosion resistance, and installation performance, but the biggest drawback of PVC pipes is their poor cold resistance and low-temperature impact resistance. The lower limit of the use temperature is about -15°C, which greatly limits the use of PVC pipes. In some cold areas in northern my country, PVC pipes can be used, but long-term exposure to sub-zero temperatures can easily cause the PVC pipes to become brittle, which in turn causes the PVC pipes to break.

[0004] Chinese patent document CN105038006A discloses a low-temperature brittle PVC pipe and a preparation method thereof, wherein the PVC pipe comprises the following raw material components and weight portions: 120-150 parts of PVC, 5-12 parts of toughening agent, 6-8 parts of active nano calcium carbonate, 8-12 parts of stabilizer, and 4-10 parts of APAO. The PVC pipe prepared by using the PVC pipe of the present invention has good impact resistance, cold resistance, and weather resistance, and its low-temperature brittleness is greatly improved compared with the PVC pipe in the prior art; the PVC pipe of the present invention is easy to process, and the raw material components have good homogeneity; the raw material cost and production cost of the PVC pipe are low. However, the calcium method uses the traditional calcium zinc heat stabilizer, which is easy to precipitate from the matrix during the processing of the PVC resin, resulting in reduced mechanical properties of the material. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide an environmentally friendly complex reinforced composite pipe with good cold resistance and mechanical properties. By adding an ionic complexing agent, the calcium zinc heat stabilizer can be effectively prevented from precipitating from the matrix during the processing of PVC resin.

[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0007] In the first aspect, the present invention provides an environmentally friendly complex-enhanced composite pipe, comprising the following components in parts by weight: 60-100 parts of PVC resin, 3-5 parts of ion complexing agent; the ion complexing agent is a mixture of calcium-zinc composite stabilizer, titanium dioxide, lubricant, nano-calcium carbonate, methyl acrylate, and plasticizer, and the mass ratio thereof is 4-7: 0.3-2: 0.5-2: 3-15: 3-8: 0.5-1.

[0008] Further preferably, the preparation method of the calcium-zinc composite stabilizer is as follows: modified graphene oxide, a calcium salt stabilizer, a zinc salt stabilizer, and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine are heated, stirred and mixed to obtain the calcium-zinc composite stabilizer.

[0009] Preferably, the mass ratio of the modified graphene oxide, the calcium salt stabilizer, the zinc salt stabilizer, and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine is 2-3:10-20:10-20:1-3.

[0010] Further preferably, the preparation method of the modified graphene oxide is as follows:

[0011] 1) adding graphene oxide to anhydrous ethanol for ultrasonic dispersion, adding 3-[bis(2-hydroxyethyl)aminopropane-triethoxysilane, stirring and heating for reaction, cooling and filtering after the reaction is completed, washing, and drying to obtain graphene oxide modified with an aminosilane coupling agent;

[0012] 2) Dissolve thiocarbazide in pyridine, add benzoyl chloride dropwise at 0-10°C to react, evaporate the solvent under reduced pressure, pour the residue into ice water, stir, adjust the pH to 10-11 with NaOH aqueous solution, heat to 80-100°C to react for 10-12h, evaporate the solvent to obtain a sulfur-nitrogen-containing five-membered heterocyclic compound;

[0013] 3) adding graphene oxide modified by an amino coupling agent and a sulfur-nitrogen-containing five-membered heterocyclic compound to dichloroethane, adding an aqueous sodium carbonate solution to adjust the pH value, heating to 60-85° C., reacting for 1-3 hours, cooling, and filtering to obtain the modified graphene oxide.

[0014] Preferably, in step 1), the mass ratio of graphene oxide to 3-[bis(2-hydroxyethyl)aminopropane-triethoxysilane] is 5-10:1-2.

[0015] Preferably, in step 2), the mass ratio of benzoyl chloride to thiocarbamide is 2-5:1.

[0016] Preferably, in step 3), the mass ratio of graphene oxide modified by an amino coupling agent to the sulfur- and nitrogen-containing five-membered heterocyclic compound is 3-6:1-2.

[0017] Preferably, the preparation method of the calcium salt stabilizer is as follows:

[0018] 2-octenylsuccinic anhydride and acetone are mixed and heated, and p-aminophenylacetic acid is added to react. After the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in anhydrous ethanol, sodium hydroxide is added, heated to react, and then a CaCl2 aqueous solution is added to continue the reaction, cooled and filtered, and the filter cake is collected. The filter cake is washed and dried to obtain a calcium salt stabilizer.

[0019] Preferably, the preparation method of the zinc salt stabilizer is as follows:

[0020] 2-octenylsuccinic anhydride and acetone are mixed and heated, and p-aminophenylacetic acid is added to react. After the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid. The light yellow solid is dissolved in anhydrous ethanol, sodium hydroxide is added, heated to react, and then a ZnSO4 aqueous solution is added to continue the reaction. The mixture is cooled and filtered, and a filter cake is collected. The filter cake is washed and dried to obtain a calcium salt stabilizer.

[0021] Preferably, the mass ratio of the 2-octenylsuccinic anhydride to p-aminophenylacetic acid is 2.5-4:1.

[0022] Preferably, the lubricant is paraffin oil.

[0023] Preferably, the plasticizer is one of dibutyl phthalate and dioctyl phthalate.

[0024] In a second aspect, the present invention also discloses a method for preparing the above-mentioned environmentally friendly complex enhanced composite pipe, comprising the following steps:

[0025] After preparing various raw materials according to the formula, the PVC resin and the ion complexing agent are evenly mixed and then extruded to obtain a tube blank, which is then pulled, vacuum heated, biaxially oriented and stretched, cooled and shaped, cut and expanded to obtain the environmentally friendly complexing enhanced composite pipe.

[0026] Preferably, the axial and radial stretching orientation rates of the biaxial orientation stretching are 200-220 mm / min.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1) The composite pipe of the present invention is prepared by a biaxial orientation stretching process using a PVC resin and an ion complexing agent. The ion complexing agent of the present invention has good compatibility with the PVC resin, and the obtained composite pipe has strong weather resistance and good impact resistance at low temperatures;

[0029] 2) The calcium salt stabilizer and zinc salt stabilizer of the present invention introduce octenyl flexible long chains into the structure, which facilitates the interpenetration, entanglement and cross-linking grafting with other materials, and helps prevent the precipitate from the matrix during the processing of PVC resin, thereby improving the thermal stability of PVC resin during the processing;

[0030] 3) The modified graphene of the present invention is obtained by grafting a five-membered heterocyclic compound containing sulfur and nitrogen atoms that can coordinate with the calcium salt stabilizer and the zinc salt stabilizer onto the coupling agent modified graphene, which greatly reduces the agglomeration of graphene and promotes its dispersion in the PVC matrix, so that the graphene surface has more action sites, which can improve the loading of graphene and the ability to combine with the material matrix, and can also load and interweave the calcium zinc stabilizer and other additives, so that the material structure is more compact and toughened and strengthened, and the loading capacity and cold resistance of the material are improved;

[0031] 4) The heteroatoms on the five-membered heterocyclic compound on the modified graphene of the present invention can effectively complex calcium ions and zinc ions, greatly inhibiting the zinc burning of PVC resin, and can effectively avoid thermal decomposition of PVC resin during processing, thereby affecting the mechanical properties of the material. DETAILED DESCRIPTION

[0032] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Some of the raw materials of the present invention come from the following sources:

[0034] PVC resin, brand name SG-5, Jinan Xiangfeng Weiye Chemical Co., Ltd.

[0035] Graphene oxide, carbon content is 99%, particle size is 8-10μm, sheet thickness is 1-5nm, Qingdao Yanhai Carbon Materials Co., Ltd.

[0036] Example 1

[0037] A method for preparing an environmentally friendly complex-enhanced composite pipe comprises the following steps:

[0038] 1000g of PVC resin and 30g of ion complexing agent are mixed evenly and placed in an extruder for extrusion molding to obtain a tube billet, and then the tube billet is pulled by a traction machine, vacuum heated at 120°C for 15min, and then biaxially oriented and stretched, with the axial and radial stretching orientation rates being 200mm / min respectively, and then cooled, shaped, cut, and expanded to obtain the environmentally friendly complexing enhanced composite pipe; the ion complexing agent is a mixture of 10g of calcium zinc composite stabilizer, 2g of titanium dioxide, 2g of paraffin oil, 8g of nano calcium carbonate, 8g of methyl acrylate, and 1g of dioctyl phthalate;

[0039] The preparation method of the calcium zinc composite stabilizer is as follows:

[0040] 2.4 g of modified graphene oxide, 12 g of calcium salt stabilizer, 12 g of zinc salt stabilizer, and 2 g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine were stirred and mixed uniformly, heated to 120° C., stirred for 2 h, and then cooled to obtain the calcium-zinc composite stabilizer;

[0041] The preparation method of the modified graphene oxide is as follows:

[0042] 1) Add 10 g of graphene oxide to 300 mL of anhydrous ethanol and disperse it ultrasonically at 100 Hz and 150 W for 10 min, add 2 g of 3-[bis(2-hydroxyethyl)aminopropane-triethoxysilane], heat and react at 75 ° C for 2 h, cool and filter after the reaction, wash with water and anhydrous ethanol in turn, and dry to obtain aminosilane coupling agent-modified graphene oxide;

[0043] 2) Dissolve 3.5 g of thiocarbazide in 150 mL of pyridine, add 11 g of benzoyl chloride at a rate of 2 drops / second at 0-10°C to react, evaporate the solvent under reduced pressure after the reaction is completed, then pour the residue into 200 g of ice water, stir, and then adjust the pH to 10 with 2 mol / L NaOH aqueous solution, then heat to 100°C for 10 hours, and evaporate the solvent to obtain an oxygen- and nitrogen-containing five-membered heterocyclic compound;

[0044] 3) adding 4.8 g of graphene oxide modified by an amino coupling agent and 1.6 g of a sulfur-nitrogen-containing five-membered heterocyclic compound to 200 mL of dichloroethane, adjusting the pH value to 9 with a 1 mol / L sodium carbonate aqueous solution, heating to 80° C. for reaction for 2 h, cooling, filtering and drying to obtain the modified graphene oxide;

[0045] The preparation method of the calcium salt stabilizer is as follows: 110g of 2-octenyl succinic anhydride and 300mL of acetone are mixed and heated to 50°C, 40.5g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 12g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 600mL of 10g / mL CaCl2 aqueous solution is added dropwise, the reaction is continued, the filter cake is collected by cooling and filtering, and the filter cake is washed with water and dried to obtain a calcium salt stabilizer; the preparation method of the zinc salt stabilizer is as follows: 110g of 2-octenyl succinic anhydride and 300mL of acetone are mixed and heated to 50°C, 40.5g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 12g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 600mL of 10g / mL CaCl2 aqueous solution is added dropwise. 10g / mL ZnSO4 aqueous solution, continue the reaction, cool and filter, collect the filter cake, wash the filter cake with water and dry it to obtain a zinc salt stabilizer.

[0046] Example 2

[0047] A method for preparing an environmentally friendly complex-enhanced composite pipe comprises the following steps:

[0048] 600g of PVC resin and 34g of ion complexing agent are mixed evenly and placed in an extruder for extrusion molding to obtain a tube billet, which is then pulled by a traction machine, vacuum heated at 100°C for 20min, and then biaxially oriented to make the axial and radial stretching orientation rates 220mm / min respectively, followed by cooling, shaping, cutting, and expanding to obtain the environmentally friendly complexing enhanced composite pipe; the ion complexing agent is a mixture of 8g of calcium zinc composite stabilizer, 1g of titanium dioxide, 1g of paraffin oil, 12g of nano calcium carbonate, 12g of methyl acrylate, and 2g of dioctyl phthalate;

[0049] The preparation method of the calcium zinc composite stabilizer is as follows:

[0050] 3 g of modified graphene oxide, 20 g of calcium salt stabilizer, 20 g of zinc salt stabilizer, and 3 g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine were stirred and mixed uniformly, heated to 100° C., stirred for 2 h, and then cooled to obtain the calcium-zinc composite stabilizer;

[0051] The preparation method of the modified graphene oxide is as follows:

[0052] 1) Add 5 g of graphene oxide to 200 mL of anhydrous ethanol and disperse it ultrasonically at 60 Hz and 120 W for 10 min, add 1 g of 3-[bis(2-hydroxyethyl)aminopropane-triethoxysilane], heat and react at 75 ° C for 2 h, cool and filter after the reaction, wash with water and anhydrous ethanol in turn, and dry to obtain graphene oxide modified with aminosilane coupling agent;

[0053] 2) Dissolve 2.8g of thiocarbazide in 150mL of pyridine, add 6g of benzoyl chloride at a rate of 2 drops / second at 0-10°C for reaction, evaporate the solvent under reduced pressure after the reaction is completed, then pour the residue into 150g of ice water, stir, and then adjust the pH to 10 with 2mol / L NaOH aqueous solution, then heat to 100°C for reaction for 10h, and evaporate the solvent to obtain an oxygen- and nitrogen-containing five-membered heterocyclic compound;

[0054] 3) adding 2.8 g of graphene oxide modified by an amino coupling agent and 1.1 g of a sulfur-nitrogen-containing five-membered heterocyclic compound to 200 mL of dichloroethane, adjusting the pH value to 9 with a 1 mol / L sodium carbonate aqueous solution, heating to 80° C. for reaction for 2 h, cooling, filtering and drying to obtain the modified graphene oxide;

[0055] The preparation method of the calcium salt stabilizer is as follows: 100g of 2-octenyl succinic anhydride and 240mL of acetone are mixed and heated to 50°C, 37.5g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 9.8g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 500mL of 10g / mL CaCl2 aqueous solution is added dropwise, the reaction is continued, the filter cake is collected by cooling and filtering, and the filter cake is washed with water and dried to obtain a calcium salt stabilizer; the preparation method of the zinc salt stabilizer is as follows: 100g of 2-octenyl succinic anhydride and 240mL of acetone are mixed and heated to 50°C, 37.5g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 9.8g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 500mL of 10g / mL CaCl2 aqueous solution is added dropwise. 10g / mL ZnSO4 aqueous solution, continue the reaction, cool and filter, collect the filter cake, wash the filter cake with water and dry it to obtain a zinc salt stabilizer.

[0056] Example 3

[0057] A method for preparing an environmentally friendly complex-enhanced composite pipe comprises the following steps:

[0058] 800g of PVC resin and 40g of ion complexing agent are mixed evenly and placed in an extruder for extrusion molding to obtain a tube billet, which is then pulled by a traction machine, vacuum heated at 110°C for 20min, and then biaxially oriented and stretched, with the axial and radial stretching orientation rates being 200mm / min respectively, followed by cooling, shaping, cutting, and expanding to obtain the environmentally friendly complexing enhanced composite pipe; the ion complexing agent is a mixture of 10g of calcium-zinc composite stabilizer, 0.6g of titanium dioxide, 1g of paraffin oil, 20.4g of nano-calcium carbonate, 8g of methyl acrylate, and 1.5g of dioctyl phthalate;

[0059] The preparation method of the calcium zinc composite stabilizer is as follows:

[0060] 2 g of modified graphene oxide, 15 g of calcium salt stabilizer, 15 g of zinc salt stabilizer, and 2 g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine were stirred and mixed uniformly, heated to 120° C., stirred for 2 h, and then cooled to obtain the calcium-zinc composite stabilizer;

[0061] The preparation method of the modified graphene oxide is as follows:

[0062] 1) 8 g of graphene oxide was added to 300 mL of anhydrous ethanol and ultrasonically dispersed at 80 Hz and 130 W for 10 min, 1.6 g of 3-[bis(2-hydroxyethyl)aminopropane-triethoxysilane was added, and the mixture was heated at 75 ° C for 2 h. After the reaction was completed, the mixture was cooled and filtered, washed with water and anhydrous ethanol in turn, and dried to obtain graphene oxide modified with an aminosilane coupling agent;

[0063] 2) Dissolve 4.3 g of thiocarbamide in 150 mL of pyridine, add 16 g of benzoyl chloride at a rate of 2 drops / second at 0-10°C to react, evaporate the solvent under reduced pressure after the reaction is completed, then pour the residue into 200 g of ice water, stir, and then adjust the pH to 10 with 2 mol / L NaOH aqueous solution, then heat to 100°C for 10 hours, and evaporate the solvent to obtain an oxygen- and nitrogen-containing five-membered heterocyclic compound;

[0064] 3) adding 4.8 g of graphene oxide modified by an amino coupling agent and 1.6 g of a sulfur-nitrogen-containing five-membered heterocyclic compound to 200 mL of dichloroethane, adjusting the pH value to 9 with a 1 mol / L sodium carbonate aqueous solution, heating to 80° C. for reaction for 2 h, cooling, filtering and drying to obtain the modified graphene oxide;

[0065] The preparation method of the calcium salt stabilizer is as follows: 130g of 2-octenyl succinic anhydride and 400mL of acetone are mixed and heated to 50°C, 48.8g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 450mL of anhydrous ethanol, 13g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 650mL of 10g / mL CaCl2 aqueous solution is added dropwise, the reaction is continued, the filter cake is collected by cooling and filtering, and the filter cake is washed with water and dried to obtain a calcium salt stabilizer; the preparation method of the zinc salt stabilizer is as follows: 130g of 2-octenyl succinic anhydride and 400mL of acetone are mixed and heated to 50°C, 48.8g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 13g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 650mL of 10g / mL CaCl2 aqueous solution is added dropwise. 10g / mL ZnSO4 aqueous solution, continue the reaction, cool and filter, collect the filter cake, wash the filter cake with water and dry it to obtain a zinc salt stabilizer.

[0066] Example 4

[0067] A method for preparing an environmentally friendly complex-enhanced composite pipe comprises the following steps:

[0068] 900g of PVC resin and 42g of ion complexing agent are mixed evenly and placed in an extruder for extrusion molding to obtain a tube billet, which is then pulled by a traction machine, vacuum heated at 120°C for 20min, and then biaxially oriented to make the axial and radial stretching orientation rates 215mm / min respectively, followed by cooling, shaping, cutting, and expanding to obtain the environmentally friendly complexing enhanced composite pipe; the ion complexing agent is a mixture of 12g of calcium zinc composite stabilizer, 2g of titanium dioxide, 2g of paraffin oil, 16g of nano calcium carbonate, 10g of methyl acrylate, and 1.5g of dioctyl phthalate;

[0069] The preparation method of the calcium zinc composite stabilizer is as follows:

[0070] 2.8 g of modified graphene oxide, 15 g of calcium salt stabilizer, 15 g of zinc salt stabilizer, and 3 g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine were stirred and mixed uniformly, heated to 120° C., stirred for 2 h, and then cooled to obtain the calcium-zinc composite stabilizer;

[0071] The preparation method of the modified graphene oxide is as follows:

[0072] 1) Add 6.8 g of graphene oxide to 280 mL of anhydrous ethanol and disperse it ultrasonically at 90 Hz and 130 W for 10 min, add 1.8 g of 3-[bis(2-hydroxyethyl)aminopropane-triethoxysilane], heat and react at 75 ° C for 2 h, cool and filter after the reaction, wash with water and anhydrous ethanol in turn, and dry to obtain graphene oxide modified with aminosilane coupling agent;

[0073] 2) Dissolve 3.2 g of thiocarbazide in 150 mL of pyridine, add 13.6 g of benzoyl chloride at a rate of 2 drops / second at 0-10°C to react, evaporate the solvent under reduced pressure after the reaction is completed, then pour the residue into 200 g of ice water, stir, and then adjust the pH to 10 with 2 mol / L NaOH aqueous solution, then heat to 100°C for 10 hours, and evaporate the solvent to obtain an oxygen- and nitrogen-containing five-membered heterocyclic compound;

[0074] 3) adding 4.5 g of graphene oxide modified by an amino coupling agent and 2.2 g of a sulfur-nitrogen-containing five-membered heterocyclic compound to 200 mL of dichloroethane, adjusting the pH value to 9 with a 1 mol / L sodium carbonate aqueous solution, heating to 80° C. for reaction for 2 h, cooling, filtering and drying to obtain the modified graphene oxide;

[0075] The preparation method of the calcium salt stabilizer is as follows: 110g of 2-octenyl succinic anhydride and 300mL of acetone are mixed and heated to 50°C, 40.5g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 12g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 600mL of 10g / mL CaCl2 aqueous solution is added dropwise, the reaction is continued, the filter cake is collected by cooling and filtering, and the filter cake is washed with water and dried to obtain a calcium salt stabilizer; the preparation method of the zinc salt stabilizer is as follows: 110g of 2-octenyl succinic anhydride and 300mL of acetone are mixed and heated to 50°C, 40.5g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 12g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 600mL of 10g / mL CaCl2 aqueous solution is added dropwise. 10g / mL ZnSO4 aqueous solution, continue the reaction, cool and filter, collect the filter cake, wash the filter cake with water and dry it to obtain a zinc salt stabilizer.

[0076] Example 5

[0077] A method for preparing an environmentally friendly complex-enhanced composite pipe comprises the following steps:

[0078] 700g of PVC resin and 48g of ion complexing agent are mixed evenly and placed in an extruder for extrusion molding to obtain a tube billet, which is then pulled by a traction machine, vacuum heated at 120°C for 15min, and then biaxially oriented and stretched, with the axial and radial stretching orientation rates being 205mm / min respectively, followed by cooling, shaping, cutting, and expanding to obtain the environmentally friendly complexing enhanced composite pipe; the ion complexing agent is a mixture of 10g of calcium-zinc composite stabilizer, 4g of titanium dioxide, 4g of paraffin oil, 14g of nano-calcium carbonate, 16g of methyl acrylate, and 2g of dioctyl phthalate;

[0079] The preparation method of the calcium zinc composite stabilizer is as follows:

[0080] 3 g of modified graphene oxide, 20 g of calcium salt stabilizer, 20 g of zinc salt stabilizer, and 3 g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine were stirred and mixed uniformly, heated to 120° C., stirred for 2 h, and then cooled to obtain the calcium-zinc composite stabilizer;

[0081] The preparation method of the modified graphene oxide is as follows:

[0082] 1) Add 5 g of graphene oxide to 300 mL of anhydrous ethanol and disperse it ultrasonically at 100 Hz and 130 W for 10 min, add 1 g of 3-[bis(2-hydroxyethyl)aminopropane-triethoxysilane, heat and react at 75 ° C for 2 h, cool and filter after the reaction, wash with water and anhydrous ethanol in turn, and dry to obtain graphene oxide modified with aminosilane coupling agent;

[0083] 2) Dissolve 3.5 g of thiocarbazide in 150 mL of pyridine, add 11 g of benzoyl chloride at a rate of 2 drops / second at 0-10°C to react, evaporate the solvent under reduced pressure after the reaction is completed, then pour the residue into 200 g of ice water, stir, and then adjust the pH to 10 with 2 mol / L NaOH aqueous solution, then heat to 100°C for 10 hours, and evaporate the solvent to obtain an oxygen- and nitrogen-containing five-membered heterocyclic compound;

[0084] 3) adding 4.8 g of graphene oxide modified by an amino coupling agent and 1.6 g of a sulfur-nitrogen-containing five-membered heterocyclic compound to 200 mL of dichloroethane, adjusting the pH value to 9 with a 1 mol / L sodium carbonate aqueous solution, heating to 80° C. for reaction for 2 h, cooling, filtering and drying to obtain the modified graphene oxide;

[0085] The preparation method of the calcium salt stabilizer is as follows: 110g of 2-octenyl succinic anhydride and 300mL of acetone are mixed and heated to 50°C, 40.5g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 12g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 600mL of 10g / mL CaCl2 aqueous solution is added dropwise, the reaction is continued, the filter cake is collected by cooling and filtering, and the filter cake is washed with water and dried to obtain a calcium salt stabilizer; the preparation method of the zinc salt stabilizer is as follows: 110g of 2-octenyl succinic anhydride and 300mL of acetone are mixed and heated to 50°C, 40.5g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 12g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 600mL of 10g / mL CaCl2 aqueous solution is added dropwise. 10g / mL ZnSO4 aqueous solution, continue the reaction, cool and filter, collect the filter cake, wash the filter cake with water and dry it to obtain a zinc salt stabilizer.

[0086] Comparative Example 1

[0087] A method for preparing an environmentally friendly complex-enhanced composite pipe comprises the following steps:

[0088] 1000g of PVC resin and 30g of ion complexing agent are mixed evenly and placed in an extruder for extrusion molding to obtain a tube billet, and then the tube billet is pulled by a traction machine, vacuum heated at 120°C for 15min, and then biaxially oriented and stretched, with the axial and radial stretching orientation rates being 200mm / min respectively, and then cooled, shaped, cut, and expanded to obtain the environmentally friendly complexing enhanced composite pipe; the ion complexing agent is a mixture of 10g of calcium zinc composite stabilizer, 2g of titanium dioxide, 2g of paraffin oil, 8g of nano calcium carbonate, 8g of methyl acrylate, and 1g of dioctyl phthalate;

[0089] The preparation method of the calcium zinc composite stabilizer is as follows:

[0090] 2.4 g of graphene oxide, 12 g of calcium salt stabilizer, 12 g of zinc salt stabilizer, and 2 g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine were stirred and mixed uniformly, heated to 120° C., stirred for 2 h, and then cooled to obtain the calcium-zinc composite stabilizer;

[0091] The preparation method of the calcium salt stabilizer is as follows: 110g of 2-octenyl succinic anhydride and 300mL of acetone are mixed and heated to 50°C, 40.5g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 12g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 600mL of 10g / mL CaCl2 aqueous solution is added dropwise, the reaction is continued, the filter cake is collected by cooling and filtering, and the filter cake is washed with water and dried to obtain a calcium salt stabilizer; the preparation method of the zinc salt stabilizer is as follows: 110g of 2-octenyl succinic anhydride and 300mL of acetone are mixed and heated to 50°C, 40.5g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 12g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 600mL of 10g / mL CaCl2 aqueous solution is added dropwise. 10g / mL ZnSO4 aqueous solution, continue the reaction, cool and filter, collect the filter cake, wash the filter cake with water and dry it to obtain a zinc salt stabilizer.

[0092] Comparative Example 2

[0093] A method for preparing an environmentally friendly complex-enhanced composite pipe comprises the following steps:

[0094] 1000g of PVC resin and 30g of ion complexing agent are mixed evenly and placed in an extruder for extrusion molding to obtain a tube billet, and then the tube billet is pulled by a traction machine, vacuum heated at 120°C for 15min, and then biaxially oriented and stretched, with the axial and radial stretching orientation rates being 200mm / min respectively, and then cooled, shaped, cut, and expanded to obtain the environmentally friendly complexing enhanced composite pipe; the ion complexing agent is a mixture of 10g of calcium zinc composite stabilizer, 2g of titanium dioxide, 2g of paraffin oil, 8g of nano calcium carbonate, 8g of methyl acrylate, and 1g of dioctyl phthalate;

[0095] The preparation method of the calcium zinc composite stabilizer is as follows:

[0096] 2.4 g of modified graphene oxide, 12 g of calcium stearate, 12 g of zinc stearate, and 2 g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine were stirred and mixed uniformly, heated to 120° C., stirred for 2 h, and then cooled to obtain the calcium-zinc composite stabilizer;

[0097] The preparation method of the modified graphene oxide is as follows:

[0098] 1) Add 10 g of graphene oxide to 300 mL of anhydrous ethanol and disperse it ultrasonically at 60-100 Hz and 120-150 W for 10 min, add 2 g of 3-[bis(2-hydroxyethyl)aminopropane-triethoxysilane, heat and react at 75 ° C for 2 h, cool and filter after the reaction, wash with water and anhydrous ethanol in turn, and dry to obtain graphene oxide modified with aminosilane coupling agent;

[0099] 2) Dissolve 3.5 g of thiocarbazide in 150 mL of pyridine, add 11 g of benzoyl chloride at a rate of 2 drops / second at 0-10°C to react, evaporate the solvent under reduced pressure after the reaction is completed, then pour the residue into 200 g of ice water, stir, and then adjust the pH to 10 with 2 mol / L NaOH aqueous solution, then heat to 100°C for 10 hours, and evaporate the solvent to obtain an oxygen- and nitrogen-containing five-membered heterocyclic compound;

[0100] 3) 4.8 g of graphene oxide modified by an amino coupling agent and 1.6 g of a sulfur-nitrogen-containing five-membered heterocyclic compound were added to 200 mL of dichloroethane, the pH value was adjusted to 9 with a 1 mol / L sodium carbonate aqueous solution, and then heated to 80° C. for reaction for 2 h, cooled, filtered, and dried to obtain the modified graphene oxide.

[0101] Comparative Example 3

[0102] A method for preparing an environmentally friendly complex-enhanced composite pipe comprises the following steps:

[0103] 1000g of PVC resin and 30g of ion complexing agent are mixed evenly and placed in an extruder for extrusion molding to obtain a tube billet, and then the tube billet is pulled by a traction machine, vacuum heated at 120°C for 15min, and then biaxially oriented and stretched, with the axial and radial stretching orientation rates being 200mm / min respectively, and then cooled, shaped, cut, and expanded to obtain the environmentally friendly complexing enhanced composite pipe; the ion complexing agent is a mixture of 10g of calcium zinc composite stabilizer, 2g of titanium dioxide, 2g of paraffin oil, 8g of nano calcium carbonate, 8g of methyl acrylate, and 1g of dioctyl phthalate;

[0104] The preparation method of the calcium zinc composite stabilizer is as follows:

[0105] 12 g of calcium salt stabilizer, 12 g of zinc salt stabilizer and 2 g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine were stirred and mixed uniformly, heated to 120° C., stirred for 2 h and then cooled to obtain the calcium-zinc composite stabilizer;

[0106] The preparation method of the calcium salt stabilizer is as follows: 110g of 2-octenyl succinic anhydride and 300mL of acetone are mixed and heated to 50°C, 40.5g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 12g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 600mL of 10g / mL CaCl2 aqueous solution is added dropwise, the reaction is continued, the filter cake is collected by cooling and filtering, and the filter cake is washed with water and dried to obtain a calcium salt stabilizer; the preparation method of the zinc salt stabilizer is as follows: 110g of 2-octenyl succinic anhydride and 300mL of acetone are mixed and heated to 50°C, 40.5g of p-aminophenylacetic acid is added to react for 3h, and after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in 350mL of anhydrous ethanol, 12g of sodium hydroxide is added, the mixture is heated to 60°C for reaction for 1h, and then 600mL of 10g / mL CaCl2 aqueous solution is added dropwise. 10g / mL ZnSO4 aqueous solution, continue the reaction, cool and filter, collect the filter cake, wash the filter cake with water and dry it to obtain a zinc salt stabilizer.

[0107] Test Case

[0108] The composite pipes prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to wear resistance, room temperature impact strength, and -30°C low temperature drop hammer impact test tests, respectively, in accordance with national standards GB / T3960-2016 (plastic sliding friction and wear test method), GB / T1843-2008 (plastic cantilever beam impact strength determination), and GB / T14152-2001 (thermoplastic plastic pipe external impact resistance test method clockwise rotation method). The results are shown in the following table:

[0109] Table 1 Composite pipe performance test results

[0110] Wear amount (mg) <![CDATA[Impact strength at normal temperature (KJ / m 3 )]]> <![CDATA[Cold resistance performance (impact drop hammer performance at -30°C) (KJ / m 3 )]]> Example 1 30.2 100.31 78.86 Example 2 31.3 95.12 73.93 Example 3 30.6 98.42 75.35 Example 4 30.8 96.39 76.68 Example 5 31.2 97.54 75.49 Comparative Example 1 40.2 70.83 50.67 Comparative Example 2 43.5 63.18 45.38 Comparative Example 3 50.3 50.26 37.89

[0111] It can be seen from the experimental data in Table 1 that the composite pipe prepared in the embodiment of the present invention has good wear resistance and good impact resistance at both normal temperature and low temperature. The difference between Comparative Examples 1-3 and Example 1 is whether a calcium salt stabilizer, a zinc salt stabilizer and a calcium-zinc composite stabilizer prepared by modified graphene are added. It can be seen that the calcium salt stabilizer, the zinc salt stabilizer and the calcium-zinc composite stabilizer prepared by modified graphene of the present invention have a greater influence on the performance of the composite pipe.

[0112] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0113] The above embodiments are only preferred technical solutions of the present invention and should not be regarded as limiting the present invention. The protection scope of the present invention shall be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.

Claims

1. An environmentally friendly complex enhanced composite pipe, characterized in that: The invention comprises the following components by weight: 60-100 parts of PVC resin and 3-5 parts of ion complexing agent; the ion complexing agent is a mixture of calcium zinc composite stabilizer, titanium dioxide, lubricant, nano calcium carbonate, methyl acrylate and plasticizer, and the mass ratio thereof is 4-7: 0.3-2: 0.5-2: 3-15: 3-8: 0.5-1; The preparation method of the calcium-zinc composite stabilizer is as follows: heating and stirring the modified graphene oxide, the calcium salt stabilizer, the zinc salt stabilizer, and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine to obtain the calcium-zinc composite stabilizer; The mass ratio of the modified graphene oxide, the calcium salt stabilizer, the zinc salt stabilizer, and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine is 2-3:10-20:10-20:1-3; The preparation method of the modified graphene oxide is as follows: 1) adding graphene oxide to anhydrous ethanol for ultrasonic dispersion, adding 3-[bis(2-hydroxyethyl)aminopropane-triethoxysilane, stirring and heating for reaction, cooling and filtering after the reaction is completed, washing, and drying to obtain graphene oxide modified with a silane coupling agent; 2) Dissolve thiocarbazide in pyridine, add benzoyl chloride dropwise at 0-10°C to react, evaporate the solvent under reduced pressure, pour the residue into ice water, stir, adjust the pH to 10-11 with NaOH aqueous solution, heat to 80-100°C to react for 10-12h, evaporate the solvent to obtain a sulfur-nitrogen-containing five-membered heterocyclic compound; 3) adding graphene oxide modified by an amino coupling agent and a sulfur-nitrogen-containing five-membered heterocyclic compound to dichloroethane, adding an aqueous sodium carbonate solution to adjust the pH value, heating to 60-85° C. and reacting for 1-3 hours, cooling, and filtering to obtain the modified graphene oxide; In the step 1), the mass ratio of graphene oxide to 3-[bis(2-hydroxyethyl)aminopropane-triethoxysilane is 5-10:1-2; In the step 2), the mass ratio of benzoyl chloride to thiocarbamide is 2-5:1; In the step 3), the mass ratio of the graphene oxide modified by the amino coupling agent to the sulfur- and nitrogen-containing five-membered heterocyclic compound is 3-6:1-2; The preparation method of the calcium salt stabilizer is as follows: 2-octenylsuccinic anhydride and acetone are mixed and heated, and p-aminophenylacetic acid is added to react. After the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid; the light yellow solid is dissolved in anhydrous ethanol, sodium hydroxide is added, heated to react, and then a CaCl2 aqueous solution is added to continue the reaction, cooled and filtered, and a filter cake is collected. The filter cake is washed and dried to obtain a calcium salt stabilizer; The preparation method of the zinc salt stabilizer is as follows: 2-octenylsuccinic anhydride and acetone are mixed and heated, and p-aminophenylacetic acid is added to react. After the reaction is completed, the solvent is evaporated under reduced pressure to obtain a light yellow solid. The light yellow solid is dissolved in anhydrous ethanol, sodium hydroxide is added, heated to react, and then a ZnSO4 aqueous solution is added to continue the reaction. The mixture is cooled and filtered, and a filter cake is collected. The filter cake is washed and dried to obtain a calcium salt stabilizer.

2. A method for preparing the composite pipe according to claim 1, characterized in that: The process comprises the following steps: uniformly mixing PVC resin and an ion complexing agent, extruding and molding the tube blank, pulling the tube blank, vacuum heating, biaxial orientation stretching, cooling and shaping, cutting and expanding the tube blank to obtain the environmentally friendly complexing enhanced composite pipe.

Citation Information

Patent Citations

  • Low-temperature-brittleness-resistant PVC pipe material and preparation method thereof

    CN105038006A

  • Low-temperature-resistant complexing enhanced PVC (polyvinyl chloride) pipe

    CN115627036A